العقل في الإسلام: منزلته، ومجالاته، وعلاقته بالنقل - Hammad Mohammed Yusuf (البصيرة: مجلة الدراسات الإسلامية, 2021)
This research aims to clarify the position of reason and its domain in Islam in view of the texts of the Qur'an and Sunnah, and to outline the concept of the relationship of reason and naql saḥīḥ, by examining the "al-Qānūn al-Kullī" conceptualized by al-Rāzī, as well as the basic explanation of its guidelines. Researchers use descriptive methods of analysis, and in some circumstances use dialectical methods according to the nature of the problem, its circumstances and implications. The results show that reason has a great position in Islam, because it is the basis of taklīf, the criteria (benchmark) of eligibility, and is one of the five maqāṣid sharia that Islam came to preserve and maintain it. Nevertheless, God has set limits for reason in istinbāṭ that cannot be exceeded, so that it does not belong in his domain: supernatural things such as the nature of asthma and the nature of God, as well as the nature of the day of resurrection. He was also unable to reveal the secret of maḥḍah worship. In fact, the position of reason in relation to revelation is like the position of sight in relation to the light of the sun, if it is in line with the light of revelation then it will be guided, otherwise it will sink into error and confusion that ends in things that are not useful. Originally, the contradiction between common sense and valid naql was impossible. However, if anyone claims this, it cannot be separated from four possibilities: damage to reason, invalid propositions, misrepresentation, or failure to distinguish between the ability of reason and its limits.